An empirical analysis of e-cigarette addiction - Xueting Deng; Yuqing Zheng; John S. Butler (Journal of Applied Economics, 2023)
This paper examines the role of addiction in influencing the demand for e-cigarettes using the Nielsen Retail Scanner Data and the Nielsen Consumer Panel Data between 2012 and 2017. With a comparison of a myopic addiction model, a forward-looking model, and a rational addiction model, this paper tests whether the consumption of e-cigarettes is addictive and rational. Results from both the macro data and the microdata support the rational addictiveness of e-cigarettes. Applying an OLS method and an instrumental variable method in causal inference, results show that the long-run price elasticity estimates are larger than the estimates of the short-run price elasticity of demand for e-cigarettes. Estimates of both long-run and short-run elasticities are greater than one, -1.50 and -1.05, suggesting e-cigarette demand is elastic in both the long run and short run.
Keywords: 330; addiction; causal inference; e-cigarettes; price elasticity of demand